An engineer's alphabet gleanings from the softer side of his profession - Petroski, Henry (Cambridge University Press, 2011)
"Written by America's most famous engineering storyteller and educator, this abecedarian is one engineer's selection of thoughts, quotations, anecdotes, facts, trivia, and arcana relating to the practice, history, culture, and traditions of his profession. The entries reflect decades of reading. writting, talking, and thinking about engineers and engineering, and range from brief essays to lists of great engineereing achievements. This work is organized alphabetically and more like a dictionary than an encyclopedia. It is not intended to be read from first page to last, but rather to be dipped into here and there as the mood strikes the reader. In time, it is hoped, this book should become the source to which readers go first when they encounter a vague or obscure reference to the softer side of engineering"--